Unravelling the TCRβ repertoire: a key to unlocking the immunopathogenesis and precision medicine in SLE - Qiao Zhou; Li Zeng; Zhixin Zhang; Jian Liu; Yichen Zhang; Yang An; Lijing Yang; Tianzuo Lan; Pengming He; Xueping Wen; Shaoping Deng (Lupus Science and Medicine)
Objectives SLE is a multifaceted autoimmune disorder with a complex pathogenesis involving genetic, environmental and hormonal factors, which converge on immune dysregulation. The T cell receptor (TCR) repertoire’s role in SLE has garnered significant interest due to its potential in both diagnostics and therapeutics. Our study aimed to delineate the variances in the TCRβ repertoire between patients with SLE and healthy individuals, correlating these differences with the severity and subtypes of SLE.Methods We conducted an analysis of blood samples from 50 treatment-naive patients with SLE and 50 healthy donors, employing RNA extraction, high-throughput sequencing and subsequent bioinformatics analysis.Results Our findings revealed significant alterations in TRBV and TRBJ gene usage frequencies, indicative of a skewed TCR repertoire in patients with SLE. Notably, nine hub TRBV genes were identified as potential biomarkers for SLE with high diagnostic accuracy. Furthermore, we observed a reduction in TCR diversity, characterised by a lower diversity 50 value and increased clonal expansion, which correlated with disease severity.Conclusions The TCRβ repertoire is significantly altered in SLE, with potential implications for diagnostics and therapeutics. The identified hub genes may serve as novel biomarkers for SLE, and the findings contribute to the understanding of the immunopathogenesis of the disease.